Photoferrotrophy: Remains of an Ancient Photosynthesis in Modern Environments - Camacho, Antonio; Walter, Xavier A.; Picazo, Antonio; Zopfi, Jakob (Frontiers in Microbiology, 2017)
Photoferrotrophy, the process by which inorganic carbon is fixed into organic matter using light as an energy source and reduced iron [Fe(II)] as an electron donor, has been proposed as one of the oldest photoautotrophic metabolisms on Earth. Under the iron-rich (ferruginous) but sulfide poor conditions dominating the Archean ocean, this type of metabolism could have accounted for most of the primary production in the photic zone. Here we review the current knowledge of biogeochemical, microbial and phylogenetic aspects of photoferrotrophy, and evaluate the ecological significance of this process in ancient and modern environments. From the ferruginous conditions that prevailed during most of the Archean, the ancient ocean evolved towards euxinic (anoxic and sulfide rich) conditions and, finally, much after the advent of oxygenic photosynthesis, to a predominantly oxic environment. Under these new conditions photoferrotrophs lost importance as primary producers, and now photoferrotrophy remains as a vestige of a formerly relevant photosynthetic process. Apart from the geological record and other biogeochemical markers, modern environments resembling the redox conditions of these ancient oceans can offer insights into the past significance of photoferrotrophy and help to explain how this metabolism operated as an important source of organic carbon for the early biosphere. Iron-rich meromictic (permanently stratified) lakes can be considered as modern analogues of the ancient Archean ocean, as they present anoxic ferruginous water columns where light can still be available at the chemocline, thus offering suitable niches for photoferrotrophs. A few bacterial strains of purple bacteria as well as of green sulfur bacteria have been shown to possess photoferrotrophic capacities, and hence, could thrive in these modern Archean ocean analogues. Studies addressing the occurrence and the biogeochemical significance of photoferrotrophy in ferruginous environments have been conducted so far in lakes Matano, Pavin, La Cruz, and the Kabuno Bay of Lake Kivu. To date, only in the latter two lakes a biogeochemical role of photoferrotrophs has been confirmed. In this review we critically summarize the current knowledge on iron-driven photosynthesis, as a remain of the ancient Earth biogeochemistry.